1994
DOI: 10.1104/pp.104.4.1341
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Water Status, Endogenous Abscisic Acid Content, and Expression of rab18 Gene during the Development of Freezing Tolerance in Arabidopsis thaliana

Abstract: Treatments as diverse as exposure to low temperature (LT), exogenous abscisic acid (ABA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
156
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(168 citation statements)
references
References 31 publications
11
156
0
Order By: Relevance
“…We investigated the possible involvement of ABA in Sus gene expression by two different approaches : (1) by feeding ABA to detached leaves and (2) by using ABAdeficient Arabidopsis mutants in a cold stress experiment. ABA had little or no effect on steady-state levels of Sus1 mRNA, whereas an ABA-responsive gene (rab18) [24] that was used as a control was strongly induced by the treatment (results not shown). This confirmed that ABA was indeed taken up efficiently by the leaves via the transpiration stream.…”
Section: Role Of Aba In Sus Expressionmentioning
confidence: 96%
See 2 more Smart Citations
“…We investigated the possible involvement of ABA in Sus gene expression by two different approaches : (1) by feeding ABA to detached leaves and (2) by using ABAdeficient Arabidopsis mutants in a cold stress experiment. ABA had little or no effect on steady-state levels of Sus1 mRNA, whereas an ABA-responsive gene (rab18) [24] that was used as a control was strongly induced by the treatment (results not shown). This confirmed that ABA was indeed taken up efficiently by the leaves via the transpiration stream.…”
Section: Role Of Aba In Sus Expressionmentioning
confidence: 96%
“…Its up-regulation did not involve ABA signalling, as demonstrated by the feeding of ABA to detached leaves (results not shown) and the use of ABA-deficient mutants under cold treatment (Figure 4). rab18, an ABAresponsive gene [24] used in these studies as a control, was very strongly induced on feeding with ABA, whereas its expression was moderate in wild-type plants under cold stress. It has been shown [24] that low temperature results in only small changes in endogenous ABA level ; in accord with that, only relatively small changes in rab18 mRNA level were observed.…”
Section: Sus1 Is Induced By Changes In Leaf Osmotic Potential Via An mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of tomato group 2 LEA protein (Le4) in yeast partially ameliorated the detrimental effects of ionic and freezing stress by conferring tolerance to high concentration of KCl but not to NaCl or sorbitol (Zhang et al, 2000). However, overexpression studies undertaken using DHNs such as CAP85 (Kaye et al, 1998) as well as C. plantagineum DHN (Iturriaga and Bartels, 1992) and RAB18 (Lang et al,1994) had no effect on freezing or drought tolerance. Overproduction of citrus dehydrin (CoCOR19) in tobacco resulted in slight decrease in ion leakage under chilling and freezing stress.…”
Section: Structure and Functional Studies Of Dhnamentioning
confidence: 99%
“…Water (Ψw) and osmotic (Ψπ) potential were measured (Ling et al 1994) with leaf psychrometer L-51A connected to dewpoint microvoltmeter HR-33 T (Wescor, Logan, UT, USA). Measurements were performed at 10:00 am and 6:00 pm on the last day of growth at optimal temperature and on two consecutive days under severe cold.…”
Section: Evaluation Of Physiological Response Of Seedlings To Severe mentioning
confidence: 99%